1999
DOI: 10.1139/f99-155
|View full text |Cite
|
Sign up to set email alerts
|

Predator-induced life history shifts inDaphnia: a synthesis of studies using meta-analysis

Abstract: Daphnia respond to kairomones from a variety of predators by altering their morphology, behavior, and life history. I use the statistical technique of meta-analysis to quantitatively evaluate the results of 27 independent studies that examine various life history responses of Daphnia to kairomones released from three common predators: Chaoborus, Notonecta, and planktivorous fish. Daphnia exhibit a fundamentally different set of life history responses to Chaoborus (delayed reproduction, decreased size of first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 61 publications
9
108
2
Order By: Relevance
“…(ii) Life history and general morphology As predicted by theory and seen in many systems, genotypes from both populations increased both age and size at maturity following exposure to Chaoborus kairomones (figure 2) [28]. Analysing both size and age, the effect of cue concentration on the probability of maturation depended on population (size model: t treatmentÂpond ¼ 14.9; age model: t treatmentÂpond ¼ 5.1; table 1 and figure 2).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…(ii) Life history and general morphology As predicted by theory and seen in many systems, genotypes from both populations increased both age and size at maturity following exposure to Chaoborus kairomones (figure 2) [28]. Analysing both size and age, the effect of cue concentration on the probability of maturation depended on population (size model: t treatmentÂpond ¼ 14.9; age model: t treatmentÂpond ¼ 5.1; table 1 and figure 2).…”
Section: Resultsmentioning
confidence: 58%
“…In addition, genotypes made other phenotypic adjustments in response to predator cue, and trait expression varied between populations. This approach tells us that genotypes of D. pulex, across populations, respond similarly to predation pressure in some core traits-something we also know from metaanalyses [28]. However, it does not quantify or synthesize the multivariate change in phenotype or the magnitude of convergence (divergence).…”
Section: Discussionmentioning
confidence: 99%
“…Carter et al (2008) observed a smaller body size of D. ambigua exposed to kairomones from a mite species, indicating that the response to predators can vary according to their type and selectivity. Life-table parameters of various Daphnia species changed when the cladocerans were exposed to kairomones of different predators, such as Chaoborus, Notonecta and fish (review by Riessen, 1999); the size at first reproduction was slightly larger under the influence of Chaoborus kairomones, whereas it decreased when in contact with kairomones of the other two predators. Daphnia pulex can reach a larger size when exposed to kairomones of Chaoborus, by controlling the growth rate (Beckerman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many species of water fleas (Daphnia) respond to the presence of predators by producing morphological defences (head and tail spines) and altering life-history traits [25,26]. Specifically, Daphnia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Daphnia sp. respond within a generation to fish chemical cues (kairomones) by developing at a faster rate and investing more heavily into reproduction [25,26]. There is also evidence that parental exposure to predator cues significantly modifies the phenotypes of offspring [27 -29], though the duration of such effects is unclear.…”
Section: Introductionmentioning
confidence: 99%